(untitled) (Research, Society and Development, 2022)
Introduction: Several changes can affect the skin, causing dysfunctions in the tissue, as happens with stretch marks; these are commonly changes that occur specifically in the dermis, and come from an exacerbated stretching of the skin. When this damaging process occurs, the stretch marks appear with a reddish or pinkish hue, generating the Red Stretch Marks (ER) and later can become whitish, the Albas Stretch Marks (AE). Objective: To compare the effects of diamond peeling and microagulation on red and/or alba stretch marks. Methodology: The research is a case study evaluated as action research, was conducted through direct observation of the practices applied to the studied patient, as well as interviews, questionnaires to understand the explanations and interpretations that occurred in the observed reality. As stretch marks tend to present themselves bilaterally, a total of 04 sessions of microdermabrasion in one hemibody and microagulation in the other hemibody were performed. The intervals between sessions were 15 days, being performed in only one participant. Results: Satisfactory results were obtained as a reduction in the size of stretch marks and appearance, with positive responses also in relation to the participant’s personal satisfaction. Conclusion: Both techniques applied brought positive results in the treatment of atrophic alba striae, showing improvements in their sizes and aspects.